British Visions, African Voices: The "Imperial" and the "Colonial" in World War II. Issue 2 (August 2020) - Osborne, Myles
Abstract: This article is focused on a magazine called Jambo, which was published by the British East Africa Command for troops in its employ between 1942 and 1945. Jambo was an agglomeration of political articles, general interest stories, propaganda, cartoons, crosswords, and more, with many of its contributions authored (or drawn) by men serving in the Allied forces. Here, I use Jambo to consider notions of the "colonial" and "imperial" during the Second World War, exploring how the realities of racial segregation in the colonies fit awkwardly with imperial service. Jambo also permits us a window into the views of some hundreds of British servicemen, who wrote extensively about the Africans with whom they served, revealing the complexities and shifts in British perceptions of African peoples during the conflict. Jambo is unique in another respect: it also provided a forum for African troops. In few other publications—and even fewer with such wide circulation—could educated (but nonelite) African peoples reach thousands of British readers. Though their published letters and articles were few compared to those written by Jambo 's British authors, African writers used the venue to critique the conditions of their military service, argue about the sort of social ordering they desired in their home communities, and create an alternate narrative of the war. Like most colonial publications, Jambo had intended audiences, but also voracious, additional, alternate publics that mediated the articles which appeared in its pages. All this suggests that we might think of the colonial public sphere as both local and global, inward and outward looking, personal and communal, and situated along a continuum between colonial and imperial contexts.